101k views
4 votes
An equation is shown below: 4x + 2(x – 3) = 4x + 2x – 11 Part A: Solve the equation and write the number of solutions. Show all the steps. (6 points) Part B: Name one property you used to solve this equation. (4 points)

2 Answers

5 votes

Part A: Here are the steps I used to solve this equation-

4x + 2(x – 3) = 4x + 2x – 11

4x + 2x - 6 = 6x - 11

6x - 6 = 6x - 11

-6 = -11

Since -6 = -11 is a false statement, there is no solution.

The final number of solutions: 0

Part B: I used the distributive property of multiplication over addition.

User Doovers
by
5.6k points
5 votes

Answer:

Part A: no solution

Part B: Distributive property of multiplication over addition.

Explanation:

Part A:

4x + 2(x – 3) = 4x + 2x – 11

4x + 2x - 6 = 6x - 11

6x - 6 = 6x - 11

-6 = -11

Since -6 = -11 is a false statement, there is no solution.

Number of solutions: 0

Part B:

Property used: Distributive property of multiplication over addition.

User Kayla
by
4.6k points